The gospel for disordered lives an introduction to Christ-centered biblical counseling - Jones, Robert D. 1959-; Kellen, Kristin L.; Green, Robert Eric (Nashville B&H Publishing Group, 2021)
This volume provides an introductory guide to the theory and practice of Christ-centered biblical counseling..
Description based on publisher supplied metadata and other sources
Keywords: Electronic books